Enhanced dielectric properties due to space charge-induced interfacial polarization in multilayer polymer films. Issue 39 (3rd October 2017) - Chen, Xinyue; Tseng, Jung-Kai; Treufeld, Imre; Mackey, Matthew; Schuele, Donald E.; Li, Ruipeng; Fukuto, Masafumi; Baer, Eric; Zhu, Lei
Abstract : Interfacial polarization due to space charges enhances electrical insulation and thus breakdown strength for multilayer polymer films. Abstract : With the recent advancement of power electronics, polymer film capacitors have become increasingly important. However, the low temperature rating (up to 85 °C) and low energy density (5 J cm −3 at breakdown) of state-of-the-art biaxially oriented polypropylene (BOPP) films have been limiting factors for advanced power electronics. Based on our recent work, multilayer films (MLFs), which consist of a high energy density polymer [ e.g., poly(vinylidene fluoride) (PVDF)] and a high breakdown/low loss polymer [ e.g., polycarbonate (PC)], have shown potential to achieve high energy density (13–17 J cm −3 ), enhanced breakdown strength, high temperature tolerance, and low loss simultaneously. In this study, the dielectric properties of PC/PVDF 50/50 32- and 256-layer (32L and 256L) films were investigated. The breakdown strength of the 32L film was as high as 800 MV m −1 at room temperature, as compared to 600 MV m −1 of PVDF and 750 MV m −1 of PC. The temperature rating of the 32L film reached 120 °C, higher than that of BOPP. In addition, it was observed that the 32L film with thicker PC layers exhibited a higher breakdown strength and a lower DC conductivity than the 256L film with thinner PC layers at elevated temperatures. These differences were attributed to the difference in the interfacial polarization of space charges, which was further verified by thermally stimulated depolarization current spectroscopy. From this study, we conclude that interfacial polarization endows MLFs with the desirable dielectric properties for next generation film capacitors.